Problems of Mining Terminology in India - Singh, R. (Meta, 1986)
Abstract In 1961 the Government of India appointed a Standing Commission for Scientific and Technical Terminology to formulate principles for evolution of terminology and preparation of standard textbooks in Hindi and other Indian Languages. The Commission published several glossaries of Engineering terminology, but none of mining engineering. From 1943 to 1954, Professor Raghu Vira, the noted Indian linguist, also published quite a few special dictionaries, and for the first time collected and compiled some mining terms in his Comprehensive English-Hindi Dictionary (1981). Though these indicate a first positive move toward collecting, processing and disseminating specialised vocabularies, their authors' principles and methods of developing terminologies vary. For want of a standard terminology of mining in Hindi and a lack of understanding of terminological concepts and their interrelationships, no textbook of mining could be written in or translated into Indian languages. It is also realised that translation of mining literature should be done by mining engineer translators who understand the systems of concepts, systems of terms and principles of translation. For a wider dissemination of scientific knowledge and technical skills, development of terminologies in Indian languages on internationally accepted sound terminological principles is necessary, even though presently subject specialists communicate in English. With the present government formulating programmes to use on a large scale the new communication technology in our school system, teaching of terminology within the framework of ESP syllabus at undergraduate level is also suggested.